Implementasi Sistem Informasi Penerimaan Peserta Didik Baru Berbasis Web Dengan Framework Codeigniter Dan Metode Waterfall (Studi Kasus : SD Negeri 1 Waled Kota) - Dwi Tegar Hartonika, Ficka; Supiyan, Dede (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Information technology is now increasingly developing, the need for quality information is very necessary. Technological developments have greatly influenced the order of life or certain rules and systems that can be utilized in various fields, one of which is education. Along with the increasingly rapid development of technology, every school should be able to make good use of advances in information systems. This is proven by advances in information technology such as internet technology and websites which are able to process data input and output quickly and accurately, especially in the implementation of New Student Admissions (PPDB). However, currently there are still many schools in Indonesia that have not implemented an online-based PPDB system. One of them is Waled Kota Public Elementary School. This school still uses conventional methods of conducting PPDB, where the system is still handwritten to record student data in its PPDB. In the 2020/2021 academic year there were 98 applicants and in the new academic year the school is expected to be able to accept as many as 160 prospective students. Based on the data obtained, with a system that is still conventional in the process, the performance of employees in the administration section is not optimal, wastes a lot of energy and takes a very long time to serve new student admissions, resulting in slow announcements of information for prospective new students. To overcome this problem, an information system is needed to carry out the PPDB process. With this system, it is hoped that the PPDB process can run more quickly and efficiently and the results of new student admissions can be monitored directly by prospective students, so as to improve the quality and efficiency of services provided by the school.